Kosmopolitisk Identitet Eller Globalisert Fremmedgjøring - Andersen, Per Thomas (Folia Scandinavica Posnaniensia, 2012)
In this article I argue that Scandinavian literature in the last 25 years is characterized by an exploration of postmodern conditions for identity construction. My point of departure is that the posttraditional society of late modernity can be described as a community experiencing deep unrest in the two ”nests” which provided most people with feelings of belonging and security in the traditional modern epoch, i.e. the nuclear family and the nation. I analyze two Norwegian novels, Jan Kjærstads´ Forføreren (1993) and Dag Solstads´ Armand V. Fotnoter til en uutgravd roman (2006), as examples of how postnational and cosmopolitan constellations influence both our individual lives and our collectively imagined communities. I focus on what I call click and dragnationalism, XL-nationalism, the one-man-nation and postnational war.